REPRESENTATION OF THE LACK OF COMMUNICATION ON ABSURD THEATRE:SHORT PLAY OF “ BİR İNSAN BAŞI ÜSTÜNE ÜÇ SESLİ ÜZÜNÇ” BY AZİZ NESİN - Emine Ulu Aslan (Fırat University, 2019)
"Absurd Theatre, which aims to represent inconformity between life and individual, has arisen with the negative atmosphere for humanity pursuant to the Second World War. Art movements such as Dadaism and Surrealism, which defend the role of irrational items in literary texts without accepting objective truth, and Existentialism, which struggles to make sense of the place of human life in life, are influential in the formation of Absurd theater. This new perception of theatre gave the first examples in Europe and; it stands against all conventional text and acting characteristics of traditional theatre. In this theatre type, existence struggle of humanbeing coincides with relative reality perception. The heroes of this theatre are nonadaptive, have communication problems and universal characteristics. The language used in theatre texts is the most important tool to reflect the lack of communication. The language, supported with visual images, pushes all boundaries and moves beyond functioning as a narration tool and loses its objective reality. This case puts language, the biggest symbol of the lack of communication in Absurd Theatre texts, into a fundamental contradiction against ""meaning"". Play of “Bir İnsan Başı Üstüne Üç Sesli Üzünç” by Aziz Nesin is an example of absurd theatrical texts that refer to Beckettyen characters and hope and expectation actions as well as to show the fluctuations of all feelings about human beings, reflecting body and language inconformity It is shown.İn this study, the effects of the Absurd Theater will be mentioned in Aziz Nesin's play, the themes, behaviors and narrative styles specific to this theater understanding will be examined."